Association between food allergy and otitis media with effusion in light of current knowledge - Mendes, Gonçalo (2019)
Introduction: Otitis media with effusion (OME) is a common middle ear condition in childhood with possible short- and long-term complications regarding hearing, language, cognition, and inflammatory disorders. Food allergy (FA) is also frequent in children and has a seemingly growing prevalence. It can affect several organs, including the middle ear. Objectives: To review published literature regarding the potential association of these conditions and their relative risk. Literature review: Allergy is a factor commonly associated with increased OME risk. Most literature on the topic focuses allergic rhinitis, due to local mechanisms potentially implicated in middle ear pathology. FA mostly affects young children, with incidence peaking at one year of age, and seems to be linked to a higher risk of other future atopic manifestations, including allergic rhinitis and asthma. OME has been proposed as an atopic manifestation in the middle ear, with several authors developing clinical studies on the subject since 1958 until present. Results have been occasionally conflicting, both regarding relative prevalence rates and presence or absence of a significant correlation between OME and FA. Conclusions: Despite absence of consensus, OME and FA frequencies, as well as their potentially severe effects and often refractory course, highlight the need for clinicians to be alert to their potential association. Further clinical studies are required to clarify this important topic.